Pattern Of Serum Resistance In Uropathogenic Escherechia Coli - PRACHI SHAW,; CHANDAN KUMAR SHAW,; K. SAILEELA, (International Journal of Pharma and Bio Sciences, 2012)
Serum resistance is an important virulence marker in uropathogenic E. coli (UPEC) but its pattern with respect to commensal gastrointestinal strains is less studied. We compared the serum resistance pattern of UPEC with commensal strains in stool samples from healthy individuals. A total of 40 isolates of UPEC (test) and intestinal E. coli (control) each was obtained from patients of all age groups with symptomatic UTI infections and healthy individuals respectively. Bacterial suspension of E. coli was mixed with serum and incubated at 37°C and the viable count was determined at 0, 1, 2 and 3 hours, followed by surface plating on MacConkey agar. The percentage of strains and the mean viable colony counts in both groups were compared using the χ2 and unpaired t – test to ascertain the statistical significance in serum resistance pattern. Sixty percent of the test strains exhibited significant growth at 3 hours incubation respectively with serum compared to 12.5% for the control strains. (p value <0.0001). The mean colony count of the test strains (0.91 ± 0.27 x 105 CFU/mL) was significantly higher than the control strains (0.53 ± 0.35 x 105 CFU/mL) at 3 hours. (p value =0.0015). Serum resistance pattern in UPEC is an important virulence marker and is expressed significantly more commonly compared to commensal strains from gastrointestinal tract.